2022
DOI: 10.3390/biology11070962
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gut Microbiota and Upregulations of VPAC2 and Intestinal Tight Junctions Correlate with Anti-Inflammatory Effects of Electroacupuncture in Colitis Mice with Sleep Fragmentation

Abstract: The relationship between inflammatory bowel disease and sleep disturbances is complicated and of increasing interest. We investigated the inflammatory and immunological consequences of EA in sleep-deprived colitis and found that dextran sulfate sodium (DSS)-induced colitis in sleep-fragmented (SF) mice was more severe than that in mice with normal sleep. This increase in the severity of colitis was accompanied by reduced body weight, shortened colon length, and deteriorated disease activity index. DSS with SF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 106 publications
1
11
0
Order By: Relevance
“…The dysfunctional intestinal microflora can stimulate inflammatory response, change the intestinal mucosal permeability, affect the inflammatory factors to aggravate the cerebral ischemia injury, and then feed back to the gut and microflora, and the cycle repeats. Acupuncture and moxibustion can regulate the various links of the cerebral and intestinal axis and block this vicious cycle (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunctional intestinal microflora can stimulate inflammatory response, change the intestinal mucosal permeability, affect the inflammatory factors to aggravate the cerebral ischemia injury, and then feed back to the gut and microflora, and the cycle repeats. Acupuncture and moxibustion can regulate the various links of the cerebral and intestinal axis and block this vicious cycle (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin, as a adipocyte derived protein, can inhibit the infiltration of macrophages and the increase of pro-inflammatory cytokines, maintain intestinal homeostasis and improve intestinal barrier integrity ( Obeid et al, 2017 ), and is significantly associated with Firmicutes differential OTUs, which may be a key node between intestinal microbiota and depression ( Bai et al, 2022 ). Liu et al (2020b , 2022) found electroacupuncture restored melatonin and adiponectin levels in plasma to near-normal levels in diseased rats as a result of electroacupuncture, while it could also restore the expression of VIP and its VIP type 1 receptor (VPAC1) and its VIP type 2 receptor (VPAC2). In addition, there is evidence that VIP can improve the immunity of intestinal mucosa ( Seillet et al, 2020 ), and it is also associated with biological depression ( Yu et al, 2021 ; Shukla et al, 2022 ), thus, acupuncture may be a mediator of gut-brain communication.…”
Section: Acupuncture Regulates Intestinal Microbiota In Psdmentioning
confidence: 99%
“…In their previous experiment, Liu et al (2020b) discovered that electroacupuncture could inhibit the proinflammatory factors IFN-γ, TNF-α, and IL-6 through TLR4 signaling via MyD88-dependent pathway to prevent excessive immune response in the whole body. According to subsequent related experiments, Liu et al (2022) also found that electroacupuncture could reduce the level of proinflammatory factor IL-6 in plasma, and significantly increase Th2/ILC2 related cytokines (including IL-4, IL-5, IL-9, IL-13, IL-10), as well as increase ILC3-derived cytokines IL-22 and GM-CSF, among which IL-10 is a potent anti-inflammatory cytokine for ILC2s to exert their functions.…”
Section: Acupuncture Regulates Intestinal Microbiota In Psdmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the innate lymphoid cells-derived cytokines (GM-CSF) were elevated in in ammatory mice colon tissue [35].…”
Section: Introductionmentioning
confidence: 99%